Impact of Fintech and Risk Management on The Sustainability Performance of MSMEs (Micro, Small and Medium Enterprises) - Safira, Safira; Agustina, Ahadiah; Hidayanti, Nur Fitri; Mukhlishin, Mukhlishin (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
This study aims to analyse the impact of Fintech and Risk Management on the Sustainability Performance of MSMEs in Mataram City. Using a quantitative approach, this study involved 100 MSMEs that have adopted Fintech services in the sub-district cakranegara and sub-district mataram areas. Data was collected through a 5-point Interval scale-based questionnaire and analysed using multiple linear regression with SPSS software version 22. The results showed that Fintech has a significant effect of 27.8% on MSME Sustainability Performance, while Risk Management has a significant effect of 53%. These findings highlight the importance of digital financial literacy and strategic risk management implementation in supporting MSME business sustainability. This research recommends MSME players to optimally utilise Fintech services and implement structured risk management. In addition, government policies are expected to facilitate digital financial literacy training and provide technical guidance on risk management for MSMEs. With this approach, Fintech will not only improve MSME competitiveness but also strengthen their business sustainability in the digital economy era. Keywords: Financial Technology (Fintech); Risk Management; Sustainability Performance MSMEs.